Impact Of Aplton Instructional Model On The Achievement Of Students In The Department Of History In Geography Subject And Developing Thier Metacognitive Skills - Hamid Al-Taee, Rana Ghanim (Opción, 2019)
The current research Investigated the impact of Using Aplton instructional model on the achievement in Geography and developing metacog nition skills for students in the Department of History. To achieve this aim, the researcher set two null hypotheses. The sample comprised (106) male and female students from 3rd year students in the Depto of History. Who were distributed random- ly among two groups equivalent in some variables such as; age (in months), IQ test, pre- learning test, and metacognition skills scale. The researcher chose (54) male and female students randomly from group C to represent the ex- periment al group In the same way, she chose (52) students from group D to represent the control group. To achieve the aim of the research the researcher prepared two instruments the First one was an achievement t-test in Iraq Ge- ography and the second was metacognition skills scale. At the end of the ex- periment, the researcher administered the two instruments up on the sample After analyzing olata, the findings show: 1- Statistical significant difference at (0.05) level of significance between the mean scores in achievement of student in the two groups and for the benefit of experimental. 2- Statistical significant difference at (0.05) level of significance between the mean scores a developing metacognition skills of students in the two groups and for the bench it of the experimented group. Accordingly, the researcher set number of recommen- dations such as:1-University lecturers should use Aplton model when teaching Geography in the departments of the collage of Humanities; as that model has positive impct in stlmulating students thinking and encouraging them to use the same model whem they will become teache vs in future and leave the tra- ditional methods in teaching. 2-Curriculum designers in the universities and instructional institution’s shlld be acquainted with fit information about the importance of Aplton instructional model to take itto considera- tion when designing the curricula and syllabus. The researcher set number of. Suggestion’s such as: -Conducting a same research, on other subject’s and academic stages, using Aplton instructional model and of ther teaching models and testing it’s impact on other dependent variables.